Increased anti-leukemic activity of decitabine via AR-42-induced upregulation of miR-29b: A novel epigenetic-targeting approach in acute myeloid leukemia - Mims, Alice (2012)
Histone deacetylase (HDAC) inhibitors either alone or in combination with hypomethylating agents have limited clinical effect in acute myeloid leukemia (AML). Previously we demonstrated that AML patients with higher miR-29b expression had better response to the hypomethylating agent decitabine. Therefore, an increase in miR-29b expression preceding decitabine treatment may provide a therapeutic advantage. We previously showed that miR-29b expression is suppressed by a repressor complex that includes HDACs. Thus, HDAC inhibition may increase miR-29b expression. We hypothesized that priming AML cells with the novel HDAC inhibitor (HDACI) AR-42 would result in increased response to decitabine treatment via upregulation of miR-29b. Here we show that AR-42 is a potent HDACI in AML, increasing miR-29b levels and leading to downregulation of known miR-29b targets (i.e., SP1, DNMT1, DNMT3A, and DNMT3B). We then demonstrated that the sequential administration of AR-42 followed by decitabine resulted in a stronger anti-leukemic activity in vitro and in vivo than decitabine followed by AR-42 or either drug alone. These preclinical results with AR-42 priming before decitabine administration represents a promising, novel treatment approach and a paradigm shift with regard to the combination of epigenetic-targeting compounds in AML, where decitabine has been traditionally given before HDAC inhibitors.